2017
DOI: 10.22192/ijcrbm.2017.02.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of total neutrophil count, neutrophil/lymphocyte ratio and left ventricular ejection fraction in predicting in- hospital mortality and complications after acute STEMI

Abstract: Background: Leukocytosis, predominantly neutrophilia has previously been described following ST elevation myocardial infarction (STEMI). The exact contribution of this phenomenon to the clinical outcome of STEMI is yet to be shown. We examined cellular inflammatory response to STEMI in the blood by assessing total neutrophil count (TNC), neutrophil to lymphocyte ratio (NLR) and Left ventricular ejection fraction (LVEF) post myocardial infarction and their association with inhospital mortality and/or adverse cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Leukocytes play a critical role in the development of AMI. It has been shown that high leukocyte levels after AMI are closely associated with higher mortality, severe ventricular arrhythmias, cardiogenic shock, and acute heart failure (17). Dharma et al (18) analyzed 585 patients with NSTEMI and found that high leukocyte levels (>11,000/μl) increased the incidence of major adverse cardiovascular events (MACE).…”
Section: Discussionmentioning
confidence: 99%
“…Leukocytes play a critical role in the development of AMI. It has been shown that high leukocyte levels after AMI are closely associated with higher mortality, severe ventricular arrhythmias, cardiogenic shock, and acute heart failure (17). Dharma et al (18) analyzed 585 patients with NSTEMI and found that high leukocyte levels (>11,000/μl) increased the incidence of major adverse cardiovascular events (MACE).…”
Section: Discussionmentioning
confidence: 99%